Author Correction: Multiscale framework for simulation-guided growth of 2D materials. (December 2018) - Momeni, Kasra; Ji, Yanzhou; Zhang, Kehao; Robinson, Joshua; Chen, Long-Qing
The Acknowledgments section of the original version of this Article did not acknowledge all of the relevant funding sources. This has now been corrected in the HTML and PDF versions of the Article.